Peningkatan Aktivitas dan Hasil Belajar Sejarah Melalui Pembelajaran Student Team Achievement Division (STAD) pada Siswa Kelas XI IPS SMA Swasta Kartika 1-4 Pematangsiantar - Harahap, Rika Rahmadhani; Zaki, Adam (Education & Learning, 2024)
This research aims to investigate the improvement of activity and learning outcomes in history subjects through the implementation of the Student Team Achievement Division (STAD) learning method among students of grade XI IPS at Kartika 1-4 Private High School in Pematangsiantar. The research method employed is classroom action research involving 40 students as participants over two cycles. Data were collected through observations of student learning activities, learning outcome tests, and student response questionnaires regarding STAD learning. The results of the study indicate that the implementation of STAD Learning can enhance the activity and learning outcomes of grade XI IPS students in history. This is evidenced by the average pre-cycle student learning activity data of 74.3, while the post-cycle II data increased to an average of 87.4. For the average score of student learning outcomes, it increased from 51 in the pre-cycle to an average score of 69.3 in cycle 1, and further increased to an average score of 87.3 in cycle II.